First Report of Florencite from the Singhbhum Shear Zone of the East Indian Craton. (3rd February 2014) - Chakraborty, Maitrayee; Biswas, Sayan; Sengupta, Nandini; Sengupta, Pulak
Abstract : Metamorphic florencite is being reported from kyanite-rich rocks from the eastern part of the Palaeo- to Mesoproterozoic Singhbhum shear zone. This is the first report of florencite from the Precambrian rocks of the Indian Shield. Host rock of florencite is a kyanite-rich rock (>80  vol%) with small and variable amounts of quartz, lazulite, augelite, and rutile. Florencite forms small (<20 microns) idioblastic-to-subhedral crystals that are included in large kyanite grains. Rarely, florencite replaces kyanite. The florencite has small proportion of crandallite (8.7–11.8 mol%) and goyazite (<2 mol%) components. Florencite of this study is dominated by Ce (~49 mol%) with significant La (~30 mol%) and Nd (~21 mol%). Compared to other florencite occurrences of the world, florencite of the studied rock is impoverished in S, Sr, and Ba and rich in P. Stability of the assemblage florencite-kyanite-augelite-lazulite and the quantitative thermobarometry in the adjoining rocks suggest that florencite was formed during Palaeoproterozoic metamorphism that culminated at theP - T range of490 ± 40 ∘ C and6.3 ± 1  kbar. Integrating all the geological features it is postulated that florencite was formed due to metasomatism of some aluminous protolith by infiltration of acidic fluids charged withPO 4 - 3 and LREE.